2012
DOI: 10.1042/cs20110627
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eclampsia and offspring cardiovascular health: mechanistic insights from experimental studies

Abstract: Pre-eclampsia is increasingly recognized as more than an isolated disease of pregnancy. Women who have had a pregnancy complicated by pre-eclampsia have a 4-fold increased risk of later cardiovascular disease. Intriguingly, the offspring of affected pregnancies also have an increased risk of higher blood pressure and almost double the risk of stroke in later life. Experimental approaches to identify the key features of pre-eclampsia responsible for this programming of offspring cardiovascular health, or the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 204 publications
(220 reference statements)
1
156
2
3
Order By: Relevance
“…19 D'Souza et al 17,[37][38][39] found that infants born later in gestation after maternal preeclampsia, a condition characterized by elevated placental-derived antiangiogenic factors in both maternal and fetal circulations, had capillary rarefaction evident at birth. 40 These observations raise the possibility that the circulating angiogenic state is both altered and directly relevant to vasculogensis in the offspring both pre-and postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…19 D'Souza et al 17,[37][38][39] found that infants born later in gestation after maternal preeclampsia, a condition characterized by elevated placental-derived antiangiogenic factors in both maternal and fetal circulations, had capillary rarefaction evident at birth. 40 These observations raise the possibility that the circulating angiogenic state is both altered and directly relevant to vasculogensis in the offspring both pre-and postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these works are the epidemiologic studies with great numbers of participants, so the results of the studies are reliable. It was found that abnormalities during pregnancy might give many pathologic consequences for future offspring's life, for example: cardiovascular and cardiopulmonary diseases, including high blood pressure and risk of stroke (1)(2)(3)(4)(5)(23)(24)(25); behavioral, neurological and mental diseases, including cerebral palsy, depression, schizophrenia, epilepsy (24,(26)(27)(28)(29)(30); metabolic diseases, including overweight, type 2 diabetes (2-5,31-33); bronchopulmonary diseases, including asthma (34,35); hearing loss (36). This data show that abnormalities during pregnancy, including obstetric complications and abnormalities of early growth, are associated with or caused by some types of hypoxia.…”
Section: Abnormalities During Pregnancy: Consequences For Future Offsmentioning
confidence: 99%
“…This susceptibility to cardiorenal and metabolic diseases post–index pregnancy has been attributed to the pathophysiological mechanisms10, 11 initiated by the placental ischemia. In addition to the maternal effects, preeclampsia is highly associated with intrauterine growth restriction12 and developmentally programs the increased risk for cardiovascular disease,13, 14 stroke,15 renal disease,16 and metabolic dysfunction17, 18 in the adult offspring of preeclamptic women 19. Since the resolution of preeclampsia is achieved only through parturition of the ischemic placenta,20 a difficult decision often must be made between inducing early delivery in order to halt the progression of the syndrome in the mother and risking premature birth complications to the fetus 21.…”
mentioning
confidence: 99%